Contribution of Transcriptome to Elucidate the Biology of Plasmodium spp - Parreira, Kleber Simônio; Scarpelli, Pedro; Rezende Lima, Wânia; Garcia, Celia R.S. (Current Topics in Medicinal Chemistry, 2022)
The present review discusses some of the new technologies that have been applied to elucidate how Plasmodium spp escape from the immune system and subvert the host physiology to orchestrate the regulation of its biological pathways. Our manuscript describes how techniques such as microarray approaches, RNA-Seq, and single-cell RNA sequencing have contributed to the discovery of transcripts and changed the concept of gene expression regulation in closely related malaria parasite species. Moreover, the text highlights the contributions of high-throughput RNA sequencing for the current knowledge of malaria parasite biology, physiology, vaccine target, and the revelation of new players in parasite signaling.
Keywords: Single-cell RNA